A Casa de Fundição de Vila Bela (1772 - 1820) - Oliveira, Náhyma Rayanne Aragão (2012)
The following dissertation privileges Foundry House of Vila Bela, with the aim to understand private and general movements of this institution’s trajectory, and analyses its role in the colonization of the far west region of Brazil – Cologne in the period of 1772 to 1820. First, we discuss the process that led to the establishment of the so-called Foundry House in Vila Bela, to bring into focus, in a later time, its internal organization. We try to understand the importance that this institution acquires in the political context of the Portuguese Empire. The Foundry House of Vila Bela will not be analysed only as an administrative body to control the charge of the fifths in Mato Grosso’s province, but also as one of the main instruments used by the Portuguese Crown to pay the defense of the western border of Brazil – Cologne and ensure the ownership of their territories against the Spanish Empire.